1997
DOI: 10.1074/jbc.272.35.22236
|View full text |Cite
|
Sign up to set email alerts
|

A Bipartite Model of 2-5A-dependent RNase L

Abstract: The 2-5A-dependent RNase (RNase L) is a tightly regulated endoribonuclease of higher vertebrates that is catalytically active only after engaging unusual effector molecules consisting of the 2,5-linked oligoadenylates, p 1-3 A(2p5A) 2 (2-5A). Progressive truncations from either terminus have provided insight into the structure, function, and regulation of RNase L. We determined that deletion of the N-terminal 335 amino acids of RNase L, about 45% of the enzyme, produced a constitutively active endoribonuclease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 20 publications
(35 reference statements)
6
129
0
1
Order By: Relevance
“…Although RNaseL does not exhibit kinase activity, it does require the lysine that coordinates ATP in kinase subdomain 2 for functional RNase activity. Deletion studies support that the carboxy-terminal region of RNaseL contains the catalytic domain and the amino terminus may negatively regulate RNaseL activity in the absence of 2Ј-5Ј oligoA (Dong and Silverman 1997).…”
Section: Ire1p Processes Hac1 Mrna By An Unprecedented Mechanismmentioning
confidence: 99%
“…Although RNaseL does not exhibit kinase activity, it does require the lysine that coordinates ATP in kinase subdomain 2 for functional RNase activity. Deletion studies support that the carboxy-terminal region of RNaseL contains the catalytic domain and the amino terminus may negatively regulate RNaseL activity in the absence of 2Ј-5Ј oligoA (Dong and Silverman 1997).…”
Section: Ire1p Processes Hac1 Mrna By An Unprecedented Mechanismmentioning
confidence: 99%
“…Binding with 2-5A induces a conformational change in the ankyrin domain of RNase L believed to unmask the C-terminal ribonuclease domain allowing homodimerization of RNase L and activation of its nuclease activity [30,[33][34][35]. The dimerization and activation of RNase L requires a molar ratio of 1:1 between RNase L and 2-5A [33,36,37].…”
Section: Ii) Rnase L Structurementioning
confidence: 99%
“…Surprisingly, the ankyrin motifs in RNase L interact with an oligonucleotide, 2-5A. Several studies with Nterminal truncations of RNase L in ankyrin motifs or mutation in the two walker A motifs have shown that R1, 7, 8, 9 are essential for 2-5A binding [1,30,31]. The crystal structure of the Nterminal ankyrin repeat domain of RNase L complexed with 2-5A shows that the bound 2-5A directly interacts with R2-R4 [17].…”
Section: I) Introductionmentioning
confidence: 99%
“…2B). 19,20 More recently, a bound ATP molecule was observed when the structure of the TRPV1 ankyrin repeats was determined by x-ray crystallography (Fig. 2C).…”
Section: Ligand Binding Properties Of Ankyrin Repeatsmentioning
confidence: 99%